Sustainable Energy Development and Agriculture in European Union Member States—Territorial Differentiation and Interrelationships - Joanna Wyrwa; Anetta Barska; Janina Jędrzejczak-Gas (Energies)
Energy is regarded as a crucial facilitator of social and economic advancement, and, consequently, sustainable development. The concept of sustainable energy development has evolved to become a significant political objective addressed by governments worldwide. All sectors of the economy, including agriculture, require stimulation, which should be triggered by linkages and structural changes contributing to qualitative and quantitative progress. Agriculture has a substantial impact on the environmental footprint, playing a pivotal role in causing climate change. The objective of this article is to address the research gap concerning the monitoring of sustainable development in the energy and agricultural sectors within the European Union. The assessment of sustainability is a complex process since it is a multidisciplinary field of study with practical implications. The progress of sustainable development in the energy and agricultural sectors was evaluated through a comprehensive analysis of relevant literature and statistical data obtained from the Eurostat database and the Research Institute of Organic Agriculture FiBL. The analysis encompasses the period between 2015 and 2022. The article employs the taxonomic method, specifically the linear ordering method (standardised sum method), which enables the construction of a synthetic measure. This approach enabled the creation of rankings and comparisons between European Union countries. The studies show that in the European Union, sustainable energy development and sustainable agriculture show significant territorial differentiation. The sustainable energy measures in the countries with the highest scores (Estonia, Sweden, Finland, Austria) were 2–3 times higher than in the countries with the lowest scores (Cyprus, Belgium, Greece, Bulgaria). A similar situation was observed for sustainable agriculture measures—the maximum measures (Estonia, Bulgaria, Slovakia, Lithuania) were about two times higher than the minimum measures (Poland, Malta, Slovenia, Luxembourg). The findings indicate that, on the one hand, there have been favourable developments at the national level in Europe, but also that there are a number of existing disparities, together with evidence of potentially significant deviations from the targets set out in the 2030 Agenda.